Hubungan Kebutuhan Emosional Dengan Kebutuhan Afeksi Pada Karyawan yang Melakukan Perilaku Seksual Hubungan Romantis di Luar Pernikahan - Maulani, Rahmi Puji; Hutahaean, Erik Saut H.; Muzzamil, Ferdy (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Extramarital romantic and sexual behavior refers to intimate or emotional interactions involving a married individual and someone other than their spouse. Among employees in long-distance relationships (LDRs) with their partners, such behavior may occur in the workplace due to unmet emotional needs. Frequent interactions with colleagues of the opposite sex, emotional closeness, and eventual physical attraction can contribute to this phenomenon. It often arises from unfulfilled emotional needs and can lead to marital conflicts, relationship deterioration, and decreased work performance. A total of 153 employees who had previously engaged in or were currently engaging in extradyadic behavior participated in the study by completing a questionnaire measuring emotional needs. The collected data were analyzed using correlation statistical techniques.